Existence d'un Equilibre General de Concurrence Imparfaite: Une Introduction - Laffont, Jean-Jacques; Laroque, Guy (Econometrica, 1976)
[This paper provides an existence proof of an oligopolistic equilibrium which solves some difficulties in the construction of a consistent descriptive model of imperfect competition.]